Astrocyte elevated gene-1 (AEG-1) is a target gene of oncogenic Ha-ras requiring phosphatidylinositol 3-kinase and c-Myc - Lee, Seok-Geun (National Academy of Sciences, 2006)
It is well established that Ha-ras and c-myc genes collaborate in promoting transformation, tumor progression, and metastasis. However, the precise mechanism underlying this cooperation remains unclear. In the present study, we document that astrocyte elevated gene-1 (AEG-1) is a downstream target molecule of Ha-ras and c-myc, mediating their tumor-promoting effects. AEG-1 expression is elevated in diverse neoplastic states, it cooperates with Ha-ras to promote transformation, and its overexpression augments invasion of transformed cells, demonstrating its functional involvement in Ha-ras-mediated tumorigenesis. We now document that AEG-1 expression is markedly induced by oncogenic Ha-ras, activating the phosphatidylinositol 3-kinase signaling pathway that augments binding of c-Myc to key E-box elements in the AEG-1 promoter, thereby regulating AEG-1 transcription. In addition, Ha-ras-mediated colony formation is inhibited by AEG-1 siRNA. This is a demonstration that Ha-ras activation of a tumor-promoting gene is regulated directly by c-Myc DNA binding via phosphatidylinositol 3-kinase signaling, thus revealing a previously uncharacterized mechanism of Ha-ras-mediated oncogenesis through AEG-1.